(untitled) (Scientia Agricola, 2001)
The grass cutting time interval affects pasture yield and morfology in terms of leaf, steam and dead material percentages. The objective of this study was to evaluate the yield, flowering time, height, structure (leaf, stem and dead material percentages) and leaf: stem ratio of a Rhodes grass (Chloris gayana Kunth.) pasture for several cutting ages. The experiment was conducted using a pasture of Piracicaba, Brazil. The experimental design consisted of completely randomized blocks, replicated four times. Treatments consisted of six cutting ages (20 to 70 days) each ten days. Increasing in yield, height, flowering, stem and dead material percentages were observed during the experimental period. Leaf percentage and leaf:stem ratio decreased during de experimental period. The cutting age affects Rhodes grass parts and yield and the optimal interval for cutting is 30 to 40 days.